Child Abuse, Neural Structure, and Adolescent Psychopathology: A Longitudinal Study - Busso, Daniel S.; McLaughlin, Katie A.; Brueck, Stephanie; Peverill, Matthew; Gold, Andrea L.; Sheridan, Margaret A. (Journal of the American Academy of Child and Adolescent Psychiatry, 2017)
Child abuse exerts a deleterious impact on a broad array of mental health outcomes. However, the neurobiological mechanisms that mediate this association remain poorly characterized. Here, we use a longitudinal design to prospectively identify neural mediators of the association between child abuse and psychiatric disorders in a community sample of adolescents. Structural magnetic resonance imaging (MRI) data and assessments of mental health were acquired for 51 adolescents (aged 13-20; M=16.96; SD=1.51), 19 of whom were exposed to physical or sexual abuse. Participants were assessed for abuse exposure (time 1), participated in MRI scanning and a diagnostic structured interview (time 2), and 2 years later were followed-up to assess psychopathology (time 3). We examined associations between child abuse and neural structure, and identified whether abuse-related differences in neural structure prospectively predicted psychiatric symptoms. Abuse was associated with reduced cortical thickness in medial and lateral prefrontal and temporal lobe regions. Thickness of the left and right parahippocampal gyrus predicted antisocial behavior symptoms, and thickness of the middle temporal gyrus predicted symptoms of generalized anxiety disorder. Thickness of the left parahippocampal gyrus mediated the longitudinal association of abuse with antisocial behavior. Child abuse is associated with widespread disruptions in cortical structure, and these disruptions are selectively associated with increased vulnerability to internalizing and externalizing psychopathology. Identifying predictive biomarkers of vulnerability following childhood maltreatment may uncover neurodevelopmental mechanisms linking environmental experience with the onset of psychopathology.